Employment outcomes of graduates: The case of Universiti Utara, Malaysia - Lim, Hock Eam (East Asian Economic Association and Blackwell Publishing Ltd., 2008)
Data on the labor market outcomes of graduates of the Universiti Utara Malaysia were analyzed using an ordered logit model. The type of degree, ethnicity, and number of job applications submitted are found to be significant determinants of labor market outcomes. Accounting graduates were found to obtain the best labor market outcomes. Malay graduates had significantly less favorable labor market outcomes. The findings for unemployed graduates support two current programs in Malaysia: re-training for the long-term unemployed and job matching assistance. The findings also suggest that universities should monitor the skill-demands of job vacancies and give specific consideration to Malay graduates.